To solve the equation \(-2.4x - 1.1 = 3.7\), we will follow the steps outlined and fill in the missing numbers.
-
Add \(1.1\) to both sides of the equation:
\[ -2.4x = 3.7 + 1.1 \]
Now calculate \(3.7 + 1.1\):
\[ 3.7 + 1.1 = 4.8 \]
Thus, we have:
\[ -2.4x = 4.8 \]
-
Divide both sides of the equation by \(-2.4\):
\[ x = \frac{4.8}{-2.4} \]
Now calculate \(\frac{4.8}{-2.4}\):
\[ x = -2 \]
Final Answers:
- The first blank is \(4.8\).
- The second blank is \(-2\).
So, the completed equations are:
\[ -2.4x = 4.8 \] \[ x = -2 \]